2022
DOI: 10.1002/trc2.12364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of traumatic brain injury on mild behavioral impairment domains prior to all‐cause dementia diagnosis and throughout disease progression

Abstract: Introduction Traumatic brain injury (TBI) may alter dementia progression, although co‐occurring neuropsychiatric symptoms (NPS) have received less attention. Originally designed to evaluate behavioral disruption prior to dementia diagnosis, the mild behavioral impairment (MBI) construct relates NPS to underlying neural circuit disruptions, with probable relevance across the progression of neurodegenerative disease. Therefore, the MBI construct may represent a valuable tool to identify and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…In a hospital-based sample, the prevalence of acute/subacute posthead injury aggression has been estimated to be 28.4%, and is often associated with new-onset major depression 29. Additionally, it has been found that sustaining a head injury before onset of dementia leads to higher rates of irritability, disinhibition, and motor disorders compared with no head injury history 6,30–32. In terms of sex differences, this study found that associations of head injury status with impairment in the impulse dyscontrol domain were stronger among females than among males.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In a hospital-based sample, the prevalence of acute/subacute posthead injury aggression has been estimated to be 28.4%, and is often associated with new-onset major depression 29. Additionally, it has been found that sustaining a head injury before onset of dementia leads to higher rates of irritability, disinhibition, and motor disorders compared with no head injury history 6,30–32. In terms of sex differences, this study found that associations of head injury status with impairment in the impulse dyscontrol domain were stronger among females than among males.…”
Section: Discussionmentioning
confidence: 65%
“…29 Additionally, it has been found that sustaining a head injury before onset of dementia leads to higher rates of irritability, disinhibition, and motor disorders compared with no head injury history. 6,[30][31][32] In terms of sex differences, this study found that associations of head injury status with impairment in the impulse dyscontrol domain were stronger among females than among males. This is consistent with a prior study from the subacute period after head injury, which found that women were more vulnerable than men to persistent mild head injuryrelated cognitive and somatic symptoms.…”
Section: Discussionmentioning
confidence: 66%
“…The consensus criteria for MBI include 5 domains, including motivation, affective regulation, impulse control, social cognition, and perception/thought, 25 and the utility of MBI has been investigated in various neurodegenerative diseases. 8,26,27 Confirmatory analyses, such as MBI construct, have the advantage of being able to explain underlying neurobiology based on previous studies. By contrast, exploratory factor analyses, as conducted in our study, are primarily data driven.…”
Section: Discussionmentioning
confidence: 99%